"Problems of learning Russian as a foreign language" (Journal of Universal Science Research, 2023)
This annotation provides a comprehensive overview of the key challenges faced by foreign learners in acquiring the Russian language. It highlights difficulties in phonetics and pronunciation, the Cyrillic alphabet, grammar complexities, vocabulary expansion, verb aspect usage, cultural context, and limited immersion opportunities. The annotation emphasizes the importance of understanding these obstacles to develop effective strategies and resources that facilitate successful language acquisition. Educators, language institutes, and learners can benefit from this annotation in designing targeted approaches to address specific difficulties, enhance the learning experience, and promote fluency in Russian as a foreign language.